Molecular characteristics and pathogenic mechanisms of KPC-3 producing hypervirulent carbapenem-resistant Klebsiella pneumoniae (ST23-K1) - Tu, Yanye; Zhao, Rongqing; Yan, Jiliang; Wu, Xingbing (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThis study aimed to comprehensively investigate hypervirulent carbapenem-resistant Klebsiella pneumoniae (CR-hvKP) in the Ningbo region. Importantly, we sought to elucidate its molecular characteristics and pathogenic mechanisms. This information will provide evidence-based insights for preventing and controlling nosocomial infections and facilitate improved clinical diagnosis and treatment in this region. Methods96 carbapenem-resistant Klebsiella pneumoniae strains were collected from the Ningbo region between January 2021 and December 2022. Whole genome sequencing and bioinformatic methods were employed to identify and characterize CR-hvKP strains at the molecular level. The minimum inhibitory concentrations (MICs) of common clinical antibiotics were determined using the VITEK-2 Compact automatic microbiological analyzer. Plasmid conjugation experiments evaluated the transferability of resistance plasmids. Finally, mouse virulence assays were conducted to explore the pathogenic mechanisms.ResultsAmong the 96 strains, a single CR-hvKP strain, designated CR-hvKP57, was identified, with an isolation frequency of 1.04%. Whole-genome sequencing revealed the strain to be ST23 serotype with a K1 capsule. This strain harbored three plasmids. Plasmid 1, a pLVPK-like virulence plasmid, carried multiple virulence genes, including rmpA, rmpA2, iroB, iucA, and terB. Plasmid 2 contained transposable element sequences such as IS15 and IS26. Plasmid 3, classified as a resistance plasmid, harbored the blaKPC-3 carbapenem resistance gene. Mouse virulence assays demonstrated a high mortality rate associated with CR-hvKP57 infection. Additionally, there was a significant increase in IL-1β, IL-6, and TNF-α levels in response to CR-hvKP57 infection, indicating varying degrees of inflammatory response. Western blot experiments further suggested that the pathogenic mechanism involves activation of the NF-κB signaling pathway.ConclusionThis study confirms the emergence of hypervirulent CR-hvKP in the Ningbo region, which likely resulted from the acquisition of a pLVPK-like virulence plasmid and a blaKPC-3 resistance plasmid by the ST23-K1 type Klebsiella pneumoniae. Our findings highlight the urgent need for more judicious use of antibiotics to limit the emergence of resistance. Additionally, strengthening infection prevention and control measures is crucial to minimize the spread of virulence and resistance plasmids.